(untitled) (gjstudies, 2018)
This research presents a novel, cross-disciplinary investigation into the evolving andunder-examined role of internal auditors within Enterprise Risk Management (ERM) frameworks. Moving beyond the traditional compliance and assurance-centric view, this paperconceptualizes internal auditors as dynamic, integrative agents who contribute to ERMthrough cognitive reframing, systemic pattern recognition, and the facilitation of organizational learning. The study employs a unique methodological hybrid, synthesizing principlesfrom computational linguistics, network theory, and behavioral economics to model andanalyze auditor contributions. We develop and apply a proprietary analytical framework,the Auditor Contribution Matrix (ACM), which quantifies contributions across four noveldimensions: Translational Efficacy, Systemic Connectivity, Cognitive Load Modulation, andResilience Amplification. Through a longitudinal case study analysis of three multinationalcorporations and a simulation model of risk information flow, we demonstrate that internalauditors, when operating within a redefined mandate, significantly enhance ERM framework adaptability, reduce systemic risk blindness, and improve strategic decision-makingalignment. Our findings challenge the prevailing paradigm of auditor objectivity as passive observation, proposing instead a model of ’engaged objectivity’ where auditors activelyshape risk understanding without compromising independence. The paper concludes thatthe most significant auditor contribution lies not in risk identification per se, but in structuring the organization’s cognitive and communicative processes for managing risk complexity,a contribution previously obscured by conventional analytical lenses. This research offers anew theoretical foundation and practical toolkit for leveraging internal audit functions as acore strategic asset within modern, complex ERM systems.